Pengaruh Pengungkapan Corporate Social Resposibility terhadap Manajemen Laba: - Melyana Sihotang; Gideon Setyo Budiwitjaksono (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to examine the effect of Corporate Social Resposibility disclosure on earnings management with the proxies Cash Flow of Operation (CFO), Production Cost (PROD), and Discretionary Expense (DISR) in manufacturing companies listed on the IDX in the 2017–2021 period. The type of research used in this study is quantitative. The number of samples in this study was 10 companies, so the total sample was 50, which were selected using the purposive sampling method. The results showed that the disclosure of Corporate Social Resposibility had no effect on earnings management with the proxies Cash Flow of Operation (CFO) and Discretionary Expense (DISR), while the disclosure of Corporate Social Resposibility had an effect on production cost (PROD). Keywords: Corporate Social Resposibility, Cash Flow of Operation, Production Cost, Discretionary Expense